2019
DOI: 10.13057/biodiv/d200803
|View full text |Cite
|
Sign up to set email alerts
|

Influences of inorganic and organic fertilizers to morphological quality attributes of Shorea macrophylla seedlings in a tropical nursery

Abstract: Abstract. Perumal M, Wasli ME, Ho SY. 2019. Influences of inorganic and organic fertilizers to morphological quality attributes of Shorea macrophylla seedlings in a tropical nursery. Biodiversitas 20: 2110-2118. Better understanding and implementation of nursery cultural regimes to improve seedling quality with high survival capability and optimal growth potential are one of the pivotal aspects of a successful forest restoration program. An experiment was set to determine the influences of inorganic and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In this study, we found that the biomass allocation pattern in both of the younger and older S. macrophylla seedlings favoured the general requirements of a balanced and healthy root system (root-to-shoot dry mass ratio < 2.0 g/g) [21] and continued to sustain this pattern in the field (Figure 2). In general, these seedlings typically had higher growth potential and were able to withstand adverse conditions (periodic inundation) at the planting sites due to the adequate root system that did not hinder plant growth.…”
Section: Effects Of Seedling Age On Growth After Outplantingmentioning
confidence: 61%
See 4 more Smart Citations
“…In this study, we found that the biomass allocation pattern in both of the younger and older S. macrophylla seedlings favoured the general requirements of a balanced and healthy root system (root-to-shoot dry mass ratio < 2.0 g/g) [21] and continued to sustain this pattern in the field (Figure 2). In general, these seedlings typically had higher growth potential and were able to withstand adverse conditions (periodic inundation) at the planting sites due to the adequate root system that did not hinder plant growth.…”
Section: Effects Of Seedling Age On Growth After Outplantingmentioning
confidence: 61%
“…Seedling Production. For seedling production, seeds of S. macrophylla were collected randomly from three identified mother trees at Sampadi Forest Reserve, Lundu, Sarawak (N01°34′13″, E109°53′12″) (Figure 1), during a masting event, which began in late January-February 2015 [21]. Seedlings for three age groups (3-, 6-, and 9-month-old) were raised under the same conditions in the Universiti Malaysia Sarawak (UNIMAS) forest research nursery (N01°27′820″, E110°27′079″) located in Kota Samarahan, Sarawak, Malaysia, from February to November 2015 (Figure 1).…”
Section: Seed Collection Preparation Of Growth Medium Andmentioning
confidence: 99%
See 3 more Smart Citations